In silico analysis and effects of environmental salinity in the expression and activity of digestive α-amylase and trypsins from the euryhaline crab Neohelice granulata - Asaro, Antonela (2017)
Studies on molecular characteristics and modulation of expression of α-amylase and trypsin in the hepatopancreas of intertidal euryhaline crabs are lacking. In this work, we cloned and studied by in silico approaches the characteristics of cDNA sequences for α-amylase and two trypsins isoforms, as well as the effect of environmental salinity, on gene expression and protein activities in the hepatopancreas of Neohelice granulata (Dana, 1851), which is a good invertebrate model species. The cDNA sequence of α-amylase is 1637 bp long, encoding 459 amino acid residues. Trypsin 1 and 2 are 689 and 1174 bp long, encoding 204 and 151 amino acid residues, respectively. Multiple sequence alignment of deduced protein sequences revealed the presence of conserved motifs found in other invertebrates. In crabs acclimated at 37 psu (hyporegulation), α-amylase mRNA level and total pancreatic amylase activity were higher than at 10 psu (hyperregulation) and 35 psu (osmoconformation). Trypsin 1 mRNA levels increased at 37 psu, while trypsin 2 levels decreased at 10 and 37 psu. Total trypsin activity was similar in all salinities. Our results showed a differential modulation of α-amylase and trypsin expression and total amylase activity by salinity acclimation, suggesting the occurrence of distinct mechanisms of regulation at different levels that could lead to digestive adjustments in relation to hyperregulation and (or) hyporegulation.